A review of alternative ways Malaysian artists approach self-portraits painting / Rosliza Abdul Rahim, Mumtaz Mokhtar and Ishak Ramli - Abdul Rahim, Rosliza; Mokhtar, Mumtaz; Ramli, Ishak (Universiti Teknologi MARA, Perak, 2023)
In general, portrait painting is a picture of similarity or likeness referring to a person, especially on the face up to shoulder level. However, portrait painting can be interpreted from a broader point of view other than the shape of the face. This study examines the development of local painters in portrait painting from the 1940s to the 2000s. Several approaches of portrait painters of the country are found through the analysis of their techniques and styles. The study found that the naturalistic approach has been developed into a variety of new styles of self-portrait painting that are more interesting over time. Indirectly, the definition of what portrait painting is, has also evolved. In fact, painters also put religious orders as one of the reference principles for producing portrait paintings.